Organization of the Greek athletic schools - Mountakis, C.; Avgerinou, V.; Kypraios, G. (Biology of Exercise, 2008)
In the school year 1988 - 99 the first «Classes of Athletic Facilitation» were established in Greece. These Classes were for young prospective athletes and were established in certain schools in addition to ordinary studies. The purpose of these Classes was to contribute to the development of the elite athlete in order for Greece to achieve the best possible performance in the Olympic Games of 1996 which it was then thought would be staged by Greece. The aim of this study was to examine whether the Classes of Athletic Facilitation actually achieved their aim. This study was carried out with the case study methodology. From our findings it may be concluded that these Classes failed to meet the expectations of their proponents, since only 9% of the Greek Olympic team of 2004 participated in them. The main reasons of that are: a) the unwillingness of the most talented athletes to attend these Classes because of their low academic standards, b) the lack of official connection between these Classes and athletic clubs and athletic federations, and c) the serious problems concerning the appointment of the teacher - coaches.